2013
DOI: 10.1021/es4029638
|View full text |Cite
|
Sign up to set email alerts
|

Chloroacetonitrile and N,2-Dichloroacetamide Formation from the Reaction of Chloroacetaldehyde and Monochloramine in Water

Abstract: Combined chlorine is increasingly being used as an alternative disinfectant to free chlorine to maintain a residual in drinking water distribution systems mainly because it would reduce the formation of regulated disinfection byproducts (DBPs) trihalomethanes and haloacetic acids. However, the use of combined chlorine could promote the formation of currently unregulated nitrogenous DBPs (N-DBPs) such as haloacetonitriles and haloacetamides that are found to be more cyto- and genotoxic than regulated DBPs. Mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 32 publications
2
70
0
Order By: Relevance
“…15 Solutions contained AOMs that were chlorinated or chloraminated in sealed 50 mL amber glass bottles at ambient temperature in the dark for a pre-determined time (24 h or 72 h). 18,19 Although many studies have focused on DCAcAm and BAcAm at relatively higher concentrations, 20,21 no studies have reported the reliability of the analytic method used in this study. 16 Ascorbic acid at a concentration of 40 mg L À1 was used to quench residual chlorine and monochloramine before DBPs analysis.…”
Section: Dbp Formation Potential Tests and Dbps Analytical Methodsmentioning
confidence: 91%
“…15 Solutions contained AOMs that were chlorinated or chloraminated in sealed 50 mL amber glass bottles at ambient temperature in the dark for a pre-determined time (24 h or 72 h). 18,19 Although many studies have focused on DCAcAm and BAcAm at relatively higher concentrations, 20,21 no studies have reported the reliability of the analytic method used in this study. 16 Ascorbic acid at a concentration of 40 mg L À1 was used to quench residual chlorine and monochloramine before DBPs analysis.…”
Section: Dbp Formation Potential Tests and Dbps Analytical Methodsmentioning
confidence: 91%
“…Other selected LMWOAs (the four saturated carboxylic acids and one aromatic acid) formed more TCM than DCAA during chloramination, indicating the molecular characteristics of LMWOAs impacted the formation of TCM and DCAA. [18,20,21]. It is known that DCAN and TCAN can hydrolyze to form DCAcAm and TCAcAm respectively, which can themselves further hydrolyze to form DCAA and TCAA, respectively ( Figure S2) [44].…”
Section: C-dbp Formationmentioning
confidence: 99%
“…Nonetheless, recent studies have reported that chloramines may provide the nitrogen in HANs and HNMs, during reactions with organic nitrogen precursors [18,19]. And, it was found that non-nitrogenous lignin phenols and chloroacetaldehyde could react with chloramines to form dichloroacetonitrile (DCAN) and chloroacetonitrile, respectively [20,21]. However, knowledge gaps remain regarding whether chloramine may also contribute the nitrogen in HAcAms, and more broadly whether chloramine can also react with non-nitrogenous precursors to produce nitrogenous HAcAms.…”
Section: Introductionmentioning
confidence: 99%
“…Trihalomethanes (THMs) were discovered as the first chemical class of DBPs in 1974. 2 Since then, research has led to the identification of emerging DBPs 37 and determination of their formation kinetics, 810 toxicity, 7,11,12 exposure, and risk assessment. 1317 To date, more than 600 DBPs have been identified, and many are reported to be cytotoxic, genotoxic, teratogenic, or carcinogenic.…”
Section: Introductionmentioning
confidence: 99%